Shear-wave velocity structure of Australia from Rayleigh-wave analysis (2014)
The elastic structure beneath Australia is shown by means of S-velocity maps for depths ranging from zero to 400 km, determined by the regionalization and inversion of Rayleigh-wave dispersion. The traces of 233 earthquakes, occurred from 1990 to 2010, have been used to obtain Rayleigh-wave dispersion data. These earthquakes were registered by 65 seismic station located in Australia and the surrounding area. The dispersion curves were obtained for periods between 5 and 250 s, by digital filtering with a combination of MFT (Multiple Filter Technique) and TVF (Time Variable Filtering), filtering techniques. Later, all seismic events (and some stations) were grouped to obtain a dispersion curve for each source-station path. These dispersion curves were regionalized and inverted according to the generalized inversion theory, to obtain shear-wave velocity models for a rectangular grid of 2.5º×2.5º mesh size. The shear-velocity structure obtained through this procedure is shown in the S-velocity maps plotted for several depths. These results agree well with the geology and other geophysical results previously obtained. The obtained S-velocity models suggest the existence of lateral and vertical heterogeneity. The zones with consolidated and old structures present greater S-velocity values than those in the other zones, although this difference can be very little or negligible in some case. Nevertheless, in the depth range of 15 to 50 km, the different Moho depths present in the study area generate the principal variation of S-velocity. A similar behaviour is found for the depth range from 65 to 180 km, in which the lithosphere-asthenosphere boundary generates the principal variations of S-velocity. Finally, it should be highlighted a new and interesting feature was obtained in this study: the definition of the base of the asthenosphere, for depths ranging from 155 to 280 km, in Australia and the surrounding area. This feature is also present in the continents: South America, Antarctica and Africa, which were part of the same super-continent Gondwanaland, in the early Mesozoic before fragmentation.ResumenLa estructura elástica bajo Australia es mostrada por medio de mapas de velocidad de onda S, para profundidades que varían desde cero a 400 km, determinada por regionalización e inversión de dispersión de ondas Rayleigh. Las trazas de 233 terremotos, ocurridos desde 1990 hasta 2010, han sido usadas para obtener datos de dispersión de ondas Rayleigh. Estos terremotos fueron registrados por 65 estaciones sísmicas localizadas en Australia y el área circundante. Las curvas de dispersión fueron obtenidas para periodos entre 5 y 250 s, por filtrado digital con una combinación de las técnicas de filtrado: MFT (técnica del filtro múltiple) y TVF (filtrado en tiempo variable). Luego, todos los eventos sísmicos (y algunas estaciones) fueron agrupados para obtener una curva de dispersión para cada trayecto fuente-estación. Estas curvas de dispersión fueron regionalizadas e invertidas de acuerdo con la teoría de la inversión generalizada, para obtener modelos de velocidad de onda de cizalla para una rejilla regular de tamaño de celda de 2.5º×2.5º. La estructura de velocidad de cizalla obtenida a través de este procedimiento es mostrada en los mapas de velocidad de onda S representados para diversas profundidades. Estos resultados concuerdan bien con la geología y otros resultados geológicos y geofísicos previamente obtenidos. Los modelos de velocidad de onda S obtenidos sugieren la existencia de heterogeneidad lateral y vertical. Las zonas con estructuras antiguas y bien consolidadas presentan mayores valores de velocidad de onda S que los correspondientes a otras zonas, aunque esta diferencia puede ser muy pequeña o despreciable en algún caso. No obstante, en el rango de profundidad de 15 a 50 km, las diferentes profundidades del Moho presentes en el área de estudio generan la principal variación de velocidad de onda S. Un comportamiento similar es encontrado par el rango de profundidad desde 65 a 180 km, en el cual la frontera litosfera-astenosfera genera la principal variación de velocidad de onda S. Finalmente, debería ser notado que una nueva e interesante característica fue obtenida en este estudio: la definición de la base de la astenosfera, para profundidades que varían desde 155 a 280 km, en Australia y el área circundante. Esta característica está también presente en los continentes: América del Sur, Antártida y África, los cuales fueron parte del mismo súper-continente: Gondwana, en el Mesozoico temprano antes de fragmentarse.